Persepsi Siswa Terhadap Pembelajaran Seni Musik Di Kelas XI IPA 4 SMA Negeri 12 Padang - Monalisa Chania; Esy Maestro (SENDRATASIK UNP, 2020)
This study aims to see and describe the students' perceptions of music art learning in SMA 12 Padang. This type of study was a qualitative with using a descriptive approach. The instrument in this study was the researcher. It was also assisted by supporting instruments such as stationery and camera. Types of data used primary and secondary. Techniques of Data collection were carried out by doing observation, interview and literature study. Techniques in analyzing data were done by collecting, classifying, describing and making data conclusion. Based on observations and interviews, there are still many things that must be addressed by the school in order to improve the students learning outcomes. Some of them are as follows: (1) The students' perception of music art learning at class XI IPA 4 in SMA 12 Padang. (2) The students attention towards music art learning. (3) The music art learning material in SMA 12 Padang. (4) The facilities and the infrastructures provided by the school that can be supported by giving invitations to students to pay more attention to the learning of music as a subject that is as important as other subjects.